Alkaline conditions better extract anti-inflammatory polysaccharides from winemaking by-products. (May 2020) - Campestrini, Luciano Henrique; Rasera, Gabriela Boscariol; de Camargo, Adriano Costa; Franchin, Marcelo; Nani, Bruno Dias; Rosalen, Pedro Luiz; Canniatti-Brazaca, Solange Guidolin; Biasoto, Aline Camarão Telles; Shahidi, Fereidoon; Alencar, Severino Matias
Abstract: Winemaking generates large amounts of by-products, a well recognized source of phenolic compounds. However, less attention has been paid to the polysaccharide-rich fraction (PRF) and effects of fractionation techniques on its potential bioactivity. Therefore, PRFs from Syrah and Tempranillo winemaking by-products were extracted under aqueous (neutral pH conditions), acidic and alkaline conditions. PRFs were screened for their monosaccharide composition, uronic acid content, homogeneity and molecular weight. Anti-inflammatory activity of PRFs were evaluated on stimulated RAW 264.7 macrophages. PRF obtained in water and/or under acidic conditions showed heterogeneous profiles. As like as in the others, a heterogeneous and complex profile was detected in extracts procured under alkaline conditions. A high content of uronic acid was found in aqueous extracts, thus indicating the presence of pectin. Pectin and hemicellulose were present in PRFs procured under acidic conditions. Alkaline conditions rendered extracts containing a complex mixture of monosaccharides, mainly xylose. This latter PRF was the only one exhibiting anti-inflammatory potential (at 100 μg/mL) by reducing the release of TNF-α and activation of NF-κB in LPS-activated RAW 264.7 macrophages, with no effect on cell viability. Regardless of the grape variety, PRFs obtained under alkaline conditions were the best option to obtain bioactive polysaccharides with potential application as a source of anti-inflammatory compounds. A complex mixture of polymers may be responsible for the anti-inflammatory effects. Finally, according to results procured by NMR, it is possible to suggest that bioactive fractions are composed of a chain of α-L-Ara f -(1 → 3) linked, β-D-Xyl p - (1 → 4), α-D-Glc p -(1 → 4) linked, α-D-Gal p A-(1 → 4), α-D-Gal-(1 → 2) forming possible RG I and RG II and xylan chains. Graphical abstract: Unlabelled Image Highlights: Polysaccharidic-rich fractions (PRFs) from winemaking by-products were prepared PRFs were extracted under aqueous, acidic and alkaline conditions PRFs obtained under alkaline showed anti-inflammatory potential PRFs reduced TNF-α release and NF-κB activation A mixture of polymers was dominant in bioactive PRFs